Adobe After Effects CC - Gyncild, Brie (Classroom in a book, 2013)
The fastest, easiest, most comprehensive way to learn Adobe After Effects CC Classroom in a Book®, the best-selling series of hands-on software training workbooks, offers what no other book or training program does-an official training series from Adobe Systems Incorporated, developed with the support of Adobe product experts. Adobe After Effects CC Classroom in a Book contains 14 lessons that cover the basics, providing countless tips and techniques to help you become more productive with the program. You can follow the book from start to finish or choose only those lessons that interest you. Purchasing this book gives you access to the downloadable lesson files you need to work through the projects in the book, and to electronic book updates covering new features that Adobe releases for Creative Cloud customers.